2020
DOI: 10.21203/rs.3.rs-31442/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What mechanisms drive uptake of family planning when integrated with childhood immunisation in Ethiopia? A realist evaluation

Abstract: Background: Maternal and child health are key priorities among the Sustainable Development Goals , which include a particular focus on reducing morbidity and mortality among women of reproductive age, newborns, and children under the age of five. Two key components of maternal and child health are family planning (FP) and immunisation. Providing these services through an integrated delivery system could increase the uptake of vaccines and modern contraceptive methods (MCMs) particularly during the post-partum … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Frequent turnover and high workload of service providers were also identi ed as major challenges to integrate FP with PHC services. Previous studies from different contexts also reported similar challenges (31,32).…”
Section: Discussionsupporting
confidence: 58%
“…Frequent turnover and high workload of service providers were also identi ed as major challenges to integrate FP with PHC services. Previous studies from different contexts also reported similar challenges (31,32).…”
Section: Discussionsupporting
confidence: 58%
“…For example, views among women ranged from disapproval of MCM use to open acknowledgment of personal covert MCM use. Respondent roles varied across study sites as the selection of participants used a purposive approach and was informed by an initial programme theory developed by programme designers and implementers [22]. For example, some of the women interviewed had two roles (both MCM user and peer influencer) and thus their perspectives might differ from the average MCM user.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were selected through a consultative process with the implementing NGO in each country. Using this process, key stakeholders were identified based on an initial programme theory of how the intervention works [22] followed by maximum variation sampling amongst identified categories of stakeholders [23]. Providers were selected based on having experience in delivering either immunisation or FP services in health facilities where the intervention was perceived to have been more, or less, well received based on monitoring data collected by the implementers.…”
Section: Data Collectionmentioning
confidence: 99%